GAME-BASED LEARNING SYSTEM FOR SECONDARY SCHOOL STUDENTS IN PHYSICS LEARNING - Low, Han Cheng (Universiti Malaysia Sarawak (UNIMAS), 2020)
In Malaysia, most of the teachers are still using traditional teaching approach to teach physics in school despite the rapid growth of educational technology. There are some issues related to physics learning in the current education system, such as the difficulty in learning physics, lack of students’ motivations to learn physics, poor academic performance of students in physics, and the weakness in traditional physics teaching approach. Game-Based Learning is a learning approach which aims to achieve specific learning outcome of learners through gaming. Game-based learning is better than traditional learning method because of its vitality and attraction to the students. Therefore, this study aims to develop a game-based learning system based on ARCS model for Form 4 students to learn physics, and the motivation level and learning achievement of the students after using the game-based learning system were examined. This study also compared the learning achievement between traditional teaching approach and game-based learning approach. The findings from this study showed that the motivation level and learning achievement of students were significantly higher after using the game-based learning system. However, there was no significant difference when comparing the learning achievement between students who used game-based learning approach and students who used traditional learning approach, due to the limitations of this study. In overall, the game-based learning system showed positive effects to the students. Last, it was hoped that the game-based learning approach should be popularized in Malaysia’s education.